Impact of Digital Leadership on Kuwaiti Hospitals’ Employees’ Performance: أثر القيادة الرقمية على أداء العاملين في المستشفيات الكويتية - Al-Faris, Mubarak Mohsen; Bani Khaled, Marei Hassan Hamad (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the Impact of Digital Leadership on Kuwaiti hospitals’ employees’ performance by using a descriptive and analytical methodology. According to statistics provided to us by the Kuwaiti Ministry of Health, the study population consists of administrators in Kuwaiti hospitals, numbering 12006. A simple random sample commensurate with the study’s objectives was drawn, numbering 372 administrators to distribute the study questionnaire to them, and 277 valid questionnaires were retrieved for analysis. It was also found that there is a statistically significant impact at the significance level (α≤0.05) of digital leadership with its dimensions (innovation, persuasion, and knowledge) on Kuwaiti hospitals’ employees’ performance. The researchers recommended that it is essential to strengthen the factors that lead to enhancing the concept of digital leadership under its essential elements in the work environment. as well as paying attention to the priorities of the impact of the digital leadership elements on the performance of employees in order to obtain a practical impact.